THE IMPLEMENTATION OF TOPICAL APPROACH TO IMPROVE STUDENTS’ SKILL IN WRITING CURRICULUM VITAE - Lestari, Dian Puji (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2023)
This research is Classroom Action Research (CAR). The data were taken from writing test to figure out the students’ skill in writing Curriculum Vitae (CV). Furthermore, the researcher used the observation technique to get the data about student’s skill in writing, students’ activities while writing, and students’ participation in the learning process. Their activities were noted by the collaborator. The researcher also used the documentation method to support and to obtain the information concerning on the learning English in general.